NGS-Panel Diagnosis Developed for the Differential Diagnosis of Idiopathic Toe Walking and Its Application for the Investigation of Possible Genetic Causes for the Gait Anomaly - Pomarino, David; Emelina, Anna; Heidrich, Jens; Rostásy, Kevin; Schirmer, Svenja; Schönfeldt, Jan O.; Thren, Anneke; Wagner, Ferdinand; Thren, Johanna Ronja; Berger, Nina (Global Medical Genetics, 2023)
Idiopathic toe walking (ITW) describes a condition affecting approximately 4.5% of children. Toe walking is an accompanying symptom for many hereditary disorders. This retrospective study uses next-generation sequencing-panel-diagnosis to investigate the feasibility of genetic testing to research the possible genetic causes of ITW and for differential diagnosis.Data were taken from our inhouse database, the minimum age for participants was 3 years. Underlying neurological or orthopaedic conditions were tested for and ruled out prior to diagnosing ITW. Patients, who experienced complications before, during or immediately after birth, children with autism, and patients toe walking less than 50% of the time were excluded.Eighty-nine patients were included in the study, in which 66 (74.2%) patients were boys and 23 (25.8%) girls. Mean age at testing was 7.7 years (range: 3–17 years). Fifteen of the 89 patients included in the study (16.9%) had a genetic variant identified as likely pathogenic or pathogenic by the genetics laboratory. Additionally, we found 129 variants of uncertain significance. About 65.2% of patients showed a pes cavus foot deformity, 27% of patients reportedly had at least one relative who also displayed the gait anomaly, and 37.1% had problems with their speech development.Despite the limitations of the sample size and the scope of our genetic testing targets, our results indicate that research into the genetic causes of ITW could better our understanding of the causes of ITW in otherwise healthy children, to help develop novel methods to detect serious conditions early. ITW could be an early onset symptom for further hereditary conditions.
Keywords: idiopathic toe walking; pes cavus; toe walking family history; cause toe walking; ITW